Weighted Gene Co-expression Network Analysis for RNA-Sequencing Data of the Varicose Veins Transcriptome - Zhang, Jianbin; Nie, Qiangqiang; Si, Chaozeng; Wang, Cheng; Chen, Yang; Sun, Weiliang; Pan, Lin; Guo, Jing; Kong, Jie; Cui, Yiyao; Wang, Feng; Fan, Xueqiang; et al. (Frontiers in Physiology, 2019)
Objective: Varicose vein is a common problem worldwide and can cause significant impairment in health related quality of life. But the etiology and pathogenesis remain not well defined. This study aims to elucidate transcriptomic regulations of varicose veins by detecting differentially expressed genes, pathways and regulator genes. Methods: We harvested normal great saphenous veins (GSV) from patients underwent coronary artery bypass grafting (CABG) and varicose veins from conventional stripping surgery. RNA-Sequencing (RNA-Seq) technique was used to obtaine the complete transcriptomic data of both normal GSV and varicose veins. Weighted Gene Co-expression network analysis (WGCNA) and further analysis was then carried out with the aim to elucidate transcriptomic regulations of varicose veins by detecting differentially expressed genes, pathways and regulator genes. Results: From January 2015 to December 2016, 7 normal GSVs and 13 varicose veins were obtained. The histopathological analysis showed in varicose veins group, the thickness of vascular wall, tunica intima, tunica media and collagen/smooth muscle ratio were significantly increased, the elastic fiber/internal elastic lamina ratio was decreased. WGCNA identified 6 modules. In grey module, biological processes were focused on response to typeⅠinterferon, cellular response to typeⅠinterferon and typeⅠinterferon signaling pathway. The molecular functions were focused on serine hydrolase activity and serine-type peptidase activity. Protein-protein interaction and further analysis showed that GBP5 and NLRP3 may be crucial in the pathogenesis of varicose veins. Conclusions: This study showed that there are clear differences in transcriptomic information between normal great saphenous veins and varicose veins. Interferons, GBP5 and NLRP3 inflammasome may play crucial rules in the pathogenesis of varicose veins, but the underlying mechanism need further investigation. Characterization of these RNAs therefore provide new targets for understanding varicose veins diagnosis, progression, and treatment.